Options to apply national developments in the assessment of sentinel lymph node involvement in breast cancer - M. V. Shomova; E. P. Kulikov; A. N. Demko; I. I. Vinogradov; A. D. Gerasimova; A. N. Budanov (ABV-press, 2024)
Background. Breast cancer is the leading oncopathology of women. The routine radical surgery performed in this pathology includes lymph node dissection, which provokes development of postmastectomy syndrome. However, the removal of non-metastatic lymph nodes is not rational according to the subsequent disability of the patients. This can be avoided by using a sentinel lymph node (SLN) biopsy procedure. At this stage of oncology development, there are several ways to visualize SLN. The fluorescent method is among the most promising. This technique has been used for many years. However, it is not sufficiently implemented in clinical practice. There are still several questions about the procedure for its performance. In addition, it requires the introduction and improvement of domestic developments, including reducing financial costs.Aim. To study the use of indocyanine green of domestic production (LLC Firm "FERMENT", Russia) and the IC-GOR detection system (LLC "MedKomplekt", Russia) for SLN biopsy in patients with early breast cancer.Materials and methods. From February to September 2023, biopsy of SLN using indocyanine green (LLC Firm "FERMENT", Russia) was performed in 53 patients with early breast cancer without clinically detectable lesion of regional lymph nodes. In all cases, according to the clinical examination, the patients had an operable stage of breast cancer (cT1-3N0M0). 5 mg of indocyanine green, dissolved in 4 ml of water for injection, was administered after sanitizing of the surgical field intradermally and subcutaneously at 2 points in the upper-outer quadrant of the breast along the edge of the areola in 40 patients (75.5 %) or paratumorally in 13 patients (24.5 %). An incision in the axilla about 4 cm long was made no earlier than 10-15 minutes after injection of indocyanine green (when visualizing the track 1 cm beyond its distal end to avoid crossing the lymph duct, after which the drug can flow into the wound). After imaging, all detected lymph nodes were removed for planned morphological examination. Standard lymph node dissection of 1 and 2 level was performed in all patients. Middle age of patients was 64.5 years (from 37 to 85 year). In 40 patients (75.5 %) modified radical mastectomy was performed, breast conserving surgery was done in 13 cases (24.5 %).Results. SLN were visualized in 51 patients out of 53 (96.2 %). After the final morphological examination, the majority of patients in the group were ranged in the IA and IIA stages of the disease - 15 (28.3 %) and 28 (52.8 %), respectively. Metastasis in the SLN were found in 9 patients (17.0 %). Besides, in 3 cases (5.7 %) metastasis in the lymph nodes were found after lymph node dissection. In 4 cases (7.6 %) metastasis were found during lymph node dissection but were not detected in the removed SLN. Thus, in the study group 13 (24.5 %) patients had metastatic lymph node lesion despite negative clinical status. The total number of removed SLN in the study group was 169 (from 1 to 6), the average number of removed lymph nodes was 3.3. Any negative events, allergic and general reactions to indocyanine were not reported.Conclusion. Our technique of contrasting SLN with indocyanine green is adequate and reproducible. The frequency of detection of SLN with this method is 96.2 %, with an acceptable level of false negative results is 7.6 %. Indocyanine green (LLC Firm "FERMENT", Russia) and the LED fluoroscopic cancer detector IC-GOR (LLC "MedKomplekt", Russia) can be recommended for performing a SLN biopsy.